Out of my real body: cognitive neuroscience meets eating disorders - Riva, Giuseppe (Frontiers in Human Neuroscience, 2014)
Clinical psychology is starting to explain eating disorders (ED) as the outcome of the interaction among cognitive, socio-emotional and interpersonal elements. In particular two influential models - the revised cognitive-interpersonal maintenance model and the transdiagnostic cognitive behavioral theory – identified possible key predisposing and maintaining factors. These models, even if very influential and able to provide clear suggestions for therapy, still are not able to provide answers to several critical questions: Why do not all the individuals with obsessive compulsive features, anxious avoidance or with a dysfunctional scheme for self-evaluation develop an eating disorder? What is the role of the body experience in the etiology of these disorders? In this paper we suggest that a meaningful answer requires the integration of these models with the recent outcomes of cognitive neuroscience. First, our bodily representations are not just a way to map an external space but the main tool we use to generate meaning, organize our experience, and shape our social identity. In particular, we will argue that our bodily experience evolves over time by integrating six different representations of the body characterized by specific pathologies – body schema (phantom limb), spatial body (unilateral hemi-neglect), active body (alien hand syndrome), personal body (autoscopic phenomena), objectified body (xenomelia) and body image (body dysmorphia). Second, these representations include either schematic (allocentric) or perceptual (egocentric) contents that interact within the working memory of the individual through the alignment between the retrieved contents from long-term memory and the ongoing egocentric contents from perception. In this view eating disorders may be the outcome of an impairment in the ability of updating a negative body representation stored in autobiographical memory (allocentric) with real-time sensorimotor and proprioceptive data (egocentric).